Sin eaters : stories - Tankersley, Caleb (Permafrost Prize series., 2022)
"Magical, heartfelt, and funny, Sin Eaters paints a picture of religion and repression while hinting at the love and connection that come with healing. The stories in Caleb Tankersley's collection illuminate the shadowy edges of the American Midwest, featuring aspects of religion, sex and desire, monsters and magic, and humor."--